Enrichment of Inflammatory IL-17 and TNF-α Secreting CD4+ T Cells within Colorectal Tumors despite the Presence of Elevated CD39+ T Regulatory Cells and Increased Expression of the Immune Checkpoint Molecule, PD-1 - Dunne, Margaret R.; Ryan, Ciara; Nolan, Bláthnaid; Tosetto, Miriam; Geraghty, Robert; Winter, Des C.; O’Connell, P. Ronan; Hyland, John M.; Doherty, Glen A.; Sheahan, Kieran; Ryan, Elizabeth J.; Fletcher, Jean M. (Frontiers in Oncology, 2016)
T cell infiltration into colorectal tumours has been shown to correlate with improved patient outcomes. However, more detailed information on the make-up and relationships between the infiltrating T cell subsets is lacking. We therefore correlated the extent of immune infiltration into colorectal tumours with the frequencies of various T cell subsets. We prospectively recruited 22 patients at the time of surgical resection for colorectal cancer. The Klintrup–Mäkinen (KM) score was used to estimate the extent of immune infiltration into colorectal tumours. The frequencies of CD4 and CD8 T cells that produced cytokines or expressed the inhibitory molecule PD-1 were determined by flow cytometry in colorectal tumour and matched uninvolved colonic tissue. In addition, the frequency of CD4 regulatory T cell subsets was determined. An increased frequency of CD4 T cells producing IL-17 (Th17 cells) was observed in colorectal tumour tissue compared with adjacent uninvolved tissue. These Th17 cells mostly co-produced TNF-α but not IFN-γ. IL-17 expression correlated positively with TNF-α and IL-10. Increased expression of the immune checkpoint molecule PD-1 was found in colorectal tumours compared with adjacent uninvolved tissue. There was a negative correlation between expression of PD-1 and IFN-γ but not IL-17, for both CD4+ and CD8+ T cells. CD4+CD25+CD127lo and CD4+CD25+CD127loFoxP3+CD39+ Treg cells were enriched in colorectal tumours. A positive correlation between KM score and percentage CD4+CD25+CD127lo Treg cells was observed in tumours suggesting that increased immune infiltration is associated with an increased proportion of Treg cells. In addition, there was a negative correlation between the frequency of CD4+CD25+CD127lo Treg cells and the expression of IFN-γ and IL-2, but not IL-17, in tumours. Taken together these data suggest that both PD-1 expressing T cells and Treg cells within the tumour may have a suppressive effect on T cells secreting IFN-γ, IL-2 or TNF-α but not Th17 cells.